Challenges of assessing the sustainability of (agro)-pastoral systems - Ayantunde, Augustine A.; Leeuw, Jan de; Turner, M.D.; Said, Mohammed Yahya (Elsevier, 2011)
Pastoralism is not only a livestock-based livelihood strategy but also a way of life with socio-cultural norms and values, and indigenous knowledge revolving around livestock. Pastoral systems in Africa are facing demographic, economic, socio-political and climatic pressures which are driving many pastoralists into non-livestock based livelihood strategies. The changing contexts in which pastoralists operate raise the issue of the sustainability of pastoral systems in dryland Africa. The specific objectives of this paper are: (i) to identify the challenges of assessing the sustainability of pastoral systems with focus on East and West Africa; (ii) to propose criteria and indicators for sustainability assessment of pastoral systems; and (iii) to demonstrate the diversity of pastoral systems by elaborating on features in East and West Africa with case studies from pastoral communities in both regions, namely Samburu in Kenya and Fakara in Niger. All these objectives are to contribute to the debates on the sustainability of pastoralism. Assessing sustainability of pastoral systems is challenging and complex in view of different aspects that should be addressed over time and at different scales. The main challenges addressed in this paper include purpose and interpretation of sustainability, time dimension and scale, diversity of pastoral systems, inter-relatedness of assessment criteria, comprehensiveness and measurability of indicators. To illustrate the challenges, we proposed a number of criteria based on key systems' components of production, stability, efficiency and resilience. For each criterion, a number of indicators were proposed. The criteria we suggested are inter-related and should not be considered in isolation bearing in mind that sustainability is a composite attribute that integrates several variables. In terms of sustainability of pastoral systems in East and West Africa, the key issues are mobility, livestock diversity, livelihood diversification options, and preservation of pastoral tradition and indigenous knowledge. The degree with which these issues are constraining pastoral production and economy will largely shape the trajectory of sustainability of different pastoral systems in both regions.